Concise rules of APA style - American Psychological Association (2010)
Concise and Bias-Free writing. Organization. Writing style. Reducing bias in language. General guidelines for reducing bias: punctuation. spelling, and capitalization. Italicizing and abbreviating. Numbers, Metrication, and statistics. Displaying results. Footnotes, Appendices, and supplemental material. Footnotes, appendices and supplemental material
Incluye bibliografía